UMP played host to Affin Bank’s Top Management - UMP, PNC
Universiti Malaysia Pahang (UMP) played host to Affin Bank and Affin Islamic Bank’s top management who came to the campus to see for themselves the progress achieved by the university as well as to hold discussion on the possibility of forming a cooperation.